1993
DOI: 10.1007/bf01296125
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyomatous colonic polyp

Abstract: Leiomyomatous colonic polyps are rare. We report a patient with an asymptomatic 15-mm submucosal polyp in the sigmoid colon. The tumor was successfully removed by endoscopy. Histopathological examination revealed a leiomyoma originating in the muscularis mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…The majority of colonic leiomyoma is asymptomatic and typically present as small polypoid intraluminal masses that can be removed endoscopically. 3,5,6 Less commonly, when symptomatic, abdominal pain is the most frequent presenting complaint, followed by a palpable mass or gastrointestinal bleeding. 4 reported another case of intraluminal leiomyoma resulting in intussusception and bowel obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of colonic leiomyoma is asymptomatic and typically present as small polypoid intraluminal masses that can be removed endoscopically. 3,5,6 Less commonly, when symptomatic, abdominal pain is the most frequent presenting complaint, followed by a palpable mass or gastrointestinal bleeding. 4 reported another case of intraluminal leiomyoma resulting in intussusception and bowel obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…2 These tumors arising from the colon are extremely rare and represent only 3 percent of all gastrointestinal leiomyomas. 3 The descending and sigmoid colon seem to be the most frequent sites of its occurrence in the colon. 4 Clinical manifestations of colonic leiomyoma depend on the size and direction of its growth.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, leiomyomas arising in the colon and rectum are rare, only 3% of all alimentary tract leiomyomas. 2 Colonic submucosal lesions, including leimyomas are usually treated by surgical resection, because endoscopic resection has a considerably higher perforation risk. 3 However, several case reports have shown that endoscopic resection of small polypoid leimyomas is feasible.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, several case reports have shown that endoscopic resection of small polypoid leimyomas is feasible. 2,[4][5][6][7][8][9][10][11][12][13] Since screening colonoscopy for colorectal cancers became widely available, the detection of small polypoid leiomyomas by colonoscopy has increased. 14 In the present study, we evaluated clinicopatho-logical characteristics of colorectal polypoid leiomyomas and the efficacy and outcome of endoscopic removal of these lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Several cases of endoscopic resection of colonic leiomyomas have been described 2 3. Because conventional polypectomy of leiomyomas can result in perforation, the technique of submucosal injection polypectomy can be used to reduce the risk of this complication.…”
Section: Introductionmentioning
confidence: 99%